The incidence of HLA-DQ2/DQ8 in Turkish children with celiac disease and a comparison of the geographical distribution of HLA-DQ - Basturk, Ahmet; Artan, Reha; Yilmaz, Aygen (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
Introduction : Celiac disease (CD) is an auto-immune enteropathy that occurs in genetically pre-disposed people as a result of the consumption of gluten-containing foods. Aim : To identify the incidence of HLA-DQ2 and HLA-DQ8 observed in children with CD. Material and methods : In this study, we focused on children ranging in age from 2 to 18 years and diagnosed with celiac disease. In our patients diagnosed with CD, in addition to tissue transglutaminase antibodies (anti-tTG), we also evaluated HLA-DQ2 B1 and HLA-DQ8 B1 alleles using the method of polymerase chain reaction (PCR)/sequence-specific oligonucleotide probes (Luminex®). The detection of 0201/0202 for HLA-DQ2 allele and 0302 for HLA-DQ8 allele was accepted as a positive result. Results : The mean age of our patients with celiac disease was 7.42 ±3.18 years, and the female/male ratio was 1.5/1. Seventy-six percent of our patients were HLA-DQ2 and/or HLA-DQ8 positive, 67% were HLA-DQ2 positive, and 25% were HLA-DQ8 positive. Nevertheless, 24% of them were HLA-DQ2 and HLA-DQ8 negative. The incidence of HLA-DQ2 in the control group was 18.8% with a significant difference compared to the HLA-DQ2 incidence in the patient group (67%) (p < 0.05). Similarly the HLA-DQ8 incidence in the control group (5.7%) was significantly lower than the incidence in the patient group (25%) (p < 0.05). Conclusions : The incidence of the patients diagnosed with CD, who are HLA-DQ2 and HLA-DQ8 negative, varies among different populations.